Effects of infrasound on the perception of a low-frequency sound - Friedrich Björn; Joost Holger; Fedtke Thomas; Verhey Jesko L. (Acta Acustica, 2023)
The study investigated the effects of an 8 Hz infrasound sinusoid, presented at a sensation level (SL) of 9 decibels (dB), on the detection of i) a 64 Hz pure tone and ii) an 8 Hz sinusoidal amplitude modulation imposed on a 64 Hz sinusoidal carrier, presented at an SL of 25 dB. Two phase relations between infrasound and amplitude modulation were used: 0° (in phase) and 180° (in antiphase). Detection thresholds of the 64 Hz pure tone were, on average across 19 normal-hearing listeners, 4.6 dB higher in the presence than in the absence of the infrasound. Modulation detection thresholds also increased in the presence of the infrasound, on average by about 3 dB. Large individual differences in modulation detection thresholds were observed with respect to the two phase relations. On average across all listeners, however, the difference in modulation detection thresholds between in-phase and antiphase infrasound was not significant. The study shows that supra-threshold infrasound masks frequency components in the low audio-frequency range and affects the perception of amplitude modulations imposed on them.